Multi-phase state estimation featuring industrial-grade distribution network models - Dzafic,I; Jabr,RA; Huseinagic,I; Pal,BC (IEEE Transactions on Smart Grid, 2016)
This paper proposes a novel implementation of a multi-phase distribution network state estimator which employs industrial-grade modeling of power components and measurements. Unlike the classical voltage-based and current-based state estimators, this paper presents the implementation details of a constrained weighted least squares state calculation method that includes standard three-phase state estimation capabilities in addition to practical modeling requirements from the industry; these requirements comprise multi-phase line configurations, unsymmetrical and incomplete transformer connections, power measurements on 4-connected loads, cumulative-type power measurements, line-to-line voltage magnitude measurements, and reversible line drop compensators. The enhanced modeling equips the estimator with capabilities that make it superior to a recently presented state-of-the-art distribution network load estimator that is currently used in real-life distribution management systems; comparative performance results demonstrate the advantage of the proposed estimator under practical measurement schemes.